FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU WANITA USIA SUBUR DALAM MELAKUKAN DETEKSI DINIKANKER PAYUDARA METODE SADARI DI WILAYAHKERJA PUSKESMAS NUSUKAN SURAKARTA - Hanifah, Anisa Nurul, Badar Kirwono, SKM, M.Kes, Anisa Catur Wijayanti, SKM., M.Epid (2015)
The death rate from breast cancer is increasing every year.Early action is early detection of breast cancer needs to be done by breast self-examination (BSE).The purpose of this study was to determine the relationship between knowledge, attitudes, family support and informationexposure with the behavior of fertile age women in the early detection of breast cancer BSE method inPuskesmas Nusukan Surakarta. This study uses obervasional analytic with cross sectional approach. This study was conducted in Puskesmas Nusukan Surakarta. The population in this study is as much as 5882fertile age women, with a total sample 147 people. Sampling using cluster random sampling. Data analysis using chi square. The results showed there was no correlation between knowledge (p-value= 0.084) and there was a relationship between attitudes (p-value= 0.005), family support (p-value= 0.001) and the informationexposure (p-value= 0.000) about the behavior of fertile age women in the early detection of breast cancer BSE method.